2008
DOI: 10.1104/pp.108.127514
|View full text |Cite
|
Sign up to set email alerts
|

Combined Proteomic and Cytological Analysis of Ca2+-Calmodulin Regulation inPicea meyeriPollen Tube Growth    

Abstract: Ca 2+ -calmodulin (Ca 2+ -CaM) is a critical molecule that mediates cellular functions by interacting with various metabolic and signaling pathways. However, the protein expression patterns and accompanying serial cytological responses in Ca 2+ -CaM signaling deficiency remain enigmatic. Here, we provide a global analysis of the cytological responses and significant alterations in protein expression profiles after trifluoperazine treatment in Picea meyeri, which abrogates Ca 2+ -CaM signaling. Ninety-three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 67 publications
(65 reference statements)
1
52
0
3
Order By: Relevance
“…It is also pertinent to mention that despite the possible non-specific effects of these antagonists, several studies carried out recently have used this system and demonstrated CaM-specific inhibition. 8,[31][32][33][34][35][36] Furthermore, the differential changes in steady state levels of Hsp70 and Hsp90 in response to Ca 2+ channel blockers and CaM, as observed in the present study, also imply that the effect of these compounds on the two classes of proteins was specific and was not the result of a general effect on all proteins.…”
Section: Methodssupporting
confidence: 72%
“…It is also pertinent to mention that despite the possible non-specific effects of these antagonists, several studies carried out recently have used this system and demonstrated CaM-specific inhibition. 8,[31][32][33][34][35][36] Furthermore, the differential changes in steady state levels of Hsp70 and Hsp90 in response to Ca 2+ channel blockers and CaM, as observed in the present study, also imply that the effect of these compounds on the two classes of proteins was specific and was not the result of a general effect on all proteins.…”
Section: Methodssupporting
confidence: 72%
“…A tipfocused gradient of cytosolic-free calcium is present in growing pollen tubes and CAM activity has been reported to display a similar tip-focused gradient (Rato et al 2004). The pivotal role played by CAM in pollen tube growth regulation has been demonstrated by the use of CAM antagonists (Rato et al 2004;Chen et al 2009) or anti-CAM antiserum (Ma et al 1999) but to our knowledge, no direct genetic evidence for a specific role for a CAM gene in pollen function was yet presented. Our data, suggesting for CAM2 a role as a Ca 2?…”
Section: Discussionmentioning
confidence: 97%
“…However, the fern spore germination happens in the medium, therefore, it is somewhat more complex and affected by various environmental factors, such as light, gravity, calcium, phytohormone, and temperature (6). The protein functional skew in fern spores and pollen grains revealed from this study and recent proteomics studies on germinating pollen from kiwifruit (Actinidia deliciosa) (71,72), Nicotiana tabacum (73), rice (Oryza sativa) (26), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78) and Arabidopsis (79,80) presented new evidence for the differentiation of fern spores and spermatophyte pollen (Fig. 10).…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 65%
“…No photosynthetic proteins were found in pollen. This highlights that the remodeling of pollen tube cell wall, the loosening and hydrolyzing stigma surface cell and transmitting track of pistil, The data of germinating pollen were summarized and reclassified based on pollen proteomic studies on Oryza sativa (26), Actinidia deliciosa (71,72), Nicotiana tabacum (73), Brassica napus (74), Pinus strobus (75), Picea meyeri (76,77), Picea wilsonii (78), and Arabidopsis thaliana (79,80). The y axis represents the reclassified functional categories, and the x axis shows the percentage of identified proteins.…”
Section: Heterotrophic and Autotrophic Metabolisms Are Active Inmentioning
confidence: 99%